ANTIOXIDANT ACTIVITY OF VARIOUS SEED EXTRACTS FROM FOUR VARIETAS OF RAMBUTAN (NEPHELIUM LAPPACEUM} L.)AND ITS CORELATTION WITH TOTAL PHENOLIC, FLAVONOID, CAROTENOID CONTENT - Fikayuniar, Lia
Many degenerative diseases related with free radical. Antioxidant is compound that can neutralize free radical. Rambutan (Nephelium lappaceum L) is one of tropical fruit from Indonesia from Sapindaceae family. Based on previous researches leaves and peels of rambutan had antioxidant activities. Different organ of one plant may contain similar compound which can give similar activity. This research aimed to determine antioxidant activity of various seed extracts from 4 varieties rambutan by determining IC50 of DPPH (2,2-diphenyl-l -picrylhydrazyl) scavenging activity and IC50 of ABTS (2,2'-azino-bis-3-ethylbenzothiazoline-6sulfonic acid), scavenging activity; total phenolic, total flavonoid, total karotenoid content in each extract analyze the correlation of total phenolic, total flavonoid, total karotenoid with IC50 DPPH and IC50 ABTS; and the correlation between IC50 DPPH and IC50 ABTS. Extraction was performed by reflux using three diferent polarities of solvents, n-hexane, ethyl acetate, and ethanol, respectively. Extracts were monitored by thin layer chromatography (TLC). Antioxidant activity of each extract was tested using DPPH and ABTS assays bydetermining IC50 of DPPH, IC50 of ABTS, determination of total phenol, flavonoid, and carotenoid content were performed by spectrophotometry UV-Vis, the correlation with IC50 of DPPH and of ABTS, and correlation between IC50 of DPPH and IC50 of ABTS by Pearson's method. The lowest IC50 of DPPH (7.09 gg/mL) was given by ethanol seed extract of lebak bulus rambutan and the lowest IC50 of ABTS (7.34 gg/mL) was shown by ethyl acetate seed extract rambutan. All of ethanol and ethyl acetate seed extracts from four varieties of rambutan had IC50 DPPH less than 50 ug/mL. Ethanolic seed extract of rapiah rambutan had the highest phenolic content (3.05 ± 0.07 g GAE / 100 g), ethyl acetate seed extract of lebak bulus rambutan had the highest flavonoid content (4.95 0.40 g QE /100 g) and ethanol seed extract of rajah rambutan had the highest carotenoid content (032 ± 0.003 g BE/IOO g). All of ethanol and ethyl acetate seed extracts of rambutan can be categorized as very strong antioxidant. Total phenolic in rapiah and-rajah seed extracts had negative, high and significant correlation with IC50 of DPPH (p < 0.01). Phenolic compounds in rapiah and rajah seed extracts were the main contributor in antioxidant activity by DPPH method. Antioxidant activity in lebak bulus, rajah and rapiah rambutan seed extracts by DPPH method gave linear result with ABTS method.